Pemindahan Penduduk Secara Paksa Dalam Konflik Bersenjata Di Filipina Dan Akibat Hukumnya Menurut Hukum Humaniter Internasional - Dio Boy Tetelepta; Arman Anwar; Richard Marsilio Waas (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Population transfer or displacement is the movement of a large group of people from one area to another, In armed conflict it is often a form of forced migration carried out by state policy or international authorities and most often on ethnic or religious grounds.Purposes of the Research: The purpose of this study is to determine and analyze the regulations prohibiting the forcible transfer of civilians in International Humanitarian Law. To know and analyze the legal impact of forcible transfer of civilians in International Humanitarian Law. Methods of the Research: The research method used in this research is normative juridical. This type of research is descriptive analytical. The sources and legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The technique of collecting legal materials through literature studies which are then processed and analyzed qualitatively.Results of the Research: The results show that the transfer of civilians in armed conflict to be used as hostages or for the purpose of winning the war at the expense of the civilian population as a living shield is a form of forced migration that is prohibited either by expulsion or other coercive actions from the area where they live without being given a reason permitted by international law. The word coercion here is not limited to physical coercion, but can include threats of violence or psychological pressure (8 paragraph (2) letters (a) and (b) of the Rome Statute and Geneva Convention IV on the Protection of Civilian Persons in Time of War). Forced population transfer or migration carried out by the Moro National Liberation Front (MNLF) to make civilians as hostages and shields in the non-international armed conflict in the Philippines.